Catalysts based on Ag nanoparticles for low-temperature СО oxidation andliquid phase selective oxidation of n-octanol; EUROPACAT 2017; Poster session 2 (P2) - Kolobova E. N. Ekaterina Nikolaevna; Pestryakov A. N. Aleksey Nikolaevich; Pakrieva E. G. Ekaterina Germanovna; Bogdanchikova N. E. Nina Evgenjevna; Cortes C V. Corberan; Kotolevich Yu. I. Yuliya (2017, 2017)
Title screen